Prevalence and associated factors of underweight, overweight and obesity among women of reproductive age group in the Maldives: Evidence from a nationally representative study - Hashan, Mohammad Rashidul; Rabbi, Md Fazla; Haider, Shams Shabab; Gupta, Rajat Das (PLOS ONE, 2022)
This article was published in PLOS ONE by BMJ Journals [© 2020 Hashan et al. This is an open access article distributed under the terms of the Creative Commons Attribution License,] and the definite version is available at: https://doi.org/10.1371/journal.pone.0241621 The Journal's website is at: https://journals.plos.org/plosone/article?id=10.1371/journal.pone.0241621